Gambaran kualitas tulang pada wanita berdasarkan kelompok usia melalui radiografi panoramik - Muhammad Fikri; Azhari Azhari; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The purpose of this research is to find out what is the average width and bone density in the neck of a condylus, in female patient using a panoramic radiograph based on age. Material and Methods: Descriptive research method was used and the sample taken in this cross sectional survey was secondary data of digital panoramic radiographs taken from patients who sought treatment in RSGM Sekeloa, Bandung for the period of January 2017 to April 2017 which were 60 female patients. The samples were divided to two groups between age 26-45 and age 46 and above as many as 30 samples per group. Results: The mean for width of neck of condyle in female patients for age 26-45 is 9.12 mm and for age 46 and above is 8.79 mm. The mean for trabecular percentage of the neck of condyle in female patients is 34.11% for age 26-45 and 33.79% for age 46 and above. Conclusion: From this study, it can be concluded that average width and density of neck condyle of women's age more than 46 years seen decrease when compared with previous age group.